2011
DOI: 10.2147/ijn.s26340
|View full text |Cite
|
Sign up to set email alerts
|

Public optimism towards nanomedicine

Abstract: Previous benefit-risk perception studies and social experiences have clearly demonstrated that any emerging technology platform that ignores benefit-risk perception by citizens might jeopardize its public acceptability and further development. The aim of this survey was to investigate the Italian judgment on nanotechnology and which demographic and heuristic variables were most influential in shaping public perceptions of the benefits and risks of nanotechnology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 26 publications
0
16
0
3
Order By: Relevance
“…2 In our study, more than half of the respondents agreed that more money should be made available for the development of genetic tests, and this percentage had not changed 27 and in particular toward the application in the screening, diagnosis and treatment of disease ('nanomedicine'). 28 It has also been shown that in contrast to more controversial biotechnological developments such as animal cloning and GM foods, higher levels of familiarity and engagement with nanotechnology over time significantly reduces worry. 29 The question remains how attitudes towards genetic testing are formed and changed.…”
Section: Discussionmentioning
confidence: 99%
“…2 In our study, more than half of the respondents agreed that more money should be made available for the development of genetic tests, and this percentage had not changed 27 and in particular toward the application in the screening, diagnosis and treatment of disease ('nanomedicine'). 28 It has also been shown that in contrast to more controversial biotechnological developments such as animal cloning and GM foods, higher levels of familiarity and engagement with nanotechnology over time significantly reduces worry. 29 The question remains how attitudes towards genetic testing are formed and changed.…”
Section: Discussionmentioning
confidence: 99%
“…They worry more about the environmental and societal risks rather than the health issues. However, people with high education, cared more about the health issues [9]. In Singapore, public were asked about the knowledge of nanotechnology, almost 80% of the respondents, have some understanding about nanotechnology [10].…”
Section: Discussionmentioning
confidence: 99%
“…(A little, some, and a lot) (8) Do you think public has awareness about application of nanotechnology used in the fi eld of medicine? (Strongly agree, agree, undecided, disagree, and strongly disagree) (9) At present, is nanomedicine effectively used in the fi eld of medicine? (Yes and no) (10) According to your knowledge does nano based treatment cause any long-term side effect?…”
Section: Nanotechnology and Nanomedicine Applicationmentioning
confidence: 99%
“…13 Few studies, however, have examined responses to nanomedicine applications as part of health care delivery. [17][18][19] A study on perceptions of nanotechnologies and nanomedicine as displayed in social media revealed that nanomedicine is expected by most users to have an economic impact and that nearly 50% of users consider theranostics to be the optimal nanomedicine application. 19 It has also been found that a medication's frequency of administration can have a greater impact on attitude toward a treatment than whether a treatment is of a nano-nature.…”
mentioning
confidence: 99%
“…As with nanotechnologies in general, nanomedicine technologies appear to be associated with public optimism tinged with concerns relating not just to health but also to impacts on the environment and on social considerations. 18 A big picture has emerged for impact perception and acceptance in relation to nanomedicine, but the lack of data on the acceptability of specific applications raises important questions about developments in this field. Will these technologies and their applications conform to individual and societal values?…”
mentioning
confidence: 99%